Aktivitas Antibakteri Ekstrak Etanol Kulit Batang Matoa (Pometia Pinnata) terhadap Pertumbuhan Staphylococcus Aureus - Litaay, Gabriela Welma (Journal of Telenursing (JOTING), 2023)
This study aims is to determine the antibacterial activity, effective concentration and content of secondary metabolite compounds from matoa (Pometia pinnata) stem bark extract against Staphylococcus aureus bacteria. The extraction was made by maceration method, while the antibacterial activity test using the diffusion agar method. The results of testing the antibacterial activity of matoa bark ethanol extract against Staphylococcus aureus were analyzed using the OneWay ANOVA test with the SPSS 26 application showing significant differences between concentrations of 1.5%, 2%, 2.5%, with positive control and negative control because the significance was < 0.05. The conclusion of this research is that there are significant differences in the concentration variations of matoa bark ethanol extract used on the growth of Staphylococcus aureus. Keywords: Antibacterial Activity, Matoa Stem Bark, Paper Disk Diffusion, Secondary Metabolites, Staphylococcus Aureus.